Flora of Bahia: Passifloraceae - Nunes, Teonildes Sacramento; Queiroz, Luciano Paganucci de (SITIENTIBUS série Ciências Biológicas, 2006)
This paper presents the result of a floristic survey of the family Passifloraceae for Bahia State, Brazil. This family is mainly tropical and subtropical, and it has about 20 genera and 650 species. It occurs mostly through warmer areas of the Americas with some species occurring in Asia and Australia, and only one specie in Madagascar. Four genera occur in Brazil: Ancistrothysus Harms, Dilkea Mast., Mitostemma Mast., and Passiflora L., with c. 120 species, most of them belonging to Passiflora. Only the genus Passiflora with 31 species was recorded in Bahia State. Among these species three are endemic from Bahia: Passiflora saxicola, P. bahiensis and P. mucugeana. Identification key, description, illustration, photos, and maps with the geographic distribution of the species in the state are presented.